VALIDITAS MEDIA PEMBELAJARAN POWERPOINT INTERAKTIF DILENGKAPI CROSSWORD PUZZLE TENTANG MATERI JARINGAN TUMBUHAN UNTUK PESERTA DIDIK SMA - Dhea Azizah; Relsas Yogica; Ganda Hijrah Selaras; Sa’diatul Fuadiyah (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2022)
Innovation in PowerPoint media determines students' interest and motivation in learning. The lack of use of game elements makes students bored. To support interactive learning, games such as crossword puzzles are needed as evaluations in the media. This study is purpose to produce interactive PowerPoint learning equipped with a crossword puzzle about plant tissue material for high school students. The research subjects is an expert validator consisting of two Biology lecturers at UNP and one Biology teacher at Payakumbuh Senior High School 3. The research used is ADDIE development research. The research was conducted up to the development stage. The analysis phase uses instruments in the form of observation sheets and interviews for teachers and students. The design stage is the design of interactive powerpoint learning media. At the development stage, using an instrument in the form of a validation sheet addressed to expert validators and analyzed. The percentage results of the three expert validations show that interactive powerpoint media is 91.90% with a very valid category. so that interactive powerpoint learning media equipped with crossword puzzles that have been developed meet the criteria and can be used by students in learning biology.